Epidemiology of Inflammatory Bowel Disease from 1981 to 2014: Results from a Territory-Wide Population-Based Registry in Hong Kong. Issue 8 (August 2016) - Ng, Siew C.; Leung, Wai Keung; Shi, Hai Yun; Li, Michael K. K.; Leung, Chi Man; Ng, Carmen K. M.; Lo, Fu Hang; Hui, Yee Tak; Tsang, Steven W. C.; Chan, Yiu Kay; Loo, Ching Kong; Chan, Kam Hon; et al.
Abstract : Background: Incidence of inflammatory bowel disease (IBD) is increasing in Asia, but population-based prevalence data are limited. This study examined IBD incidence and prevalence based on results of a territory-wide IBD registry in Hong Kong. Methods: We collected data on 2575 patients with IBD (1541 ulcerative colitis [UC], 983 Crohn's disease [CD], 51 IBD unclassified) from 1981 to 2014 using hospital and territory-wide administrative coding system. Prevalence and incidence, disease phenotype, surgery, and mortality were analyzed. Results: Adjusted prevalence of IBD, UC, CD, and IBD unclassified per 100, 000 individuals in 2014 were 44.0, 24.5, 18.6, and 0.9, respectively. Age-adjusted incidence of IBD per 100, 000 individuals increased from 0.10 (95% confidence interval, 0.06–0.16) in 1985 to 3.12 (95% confidence interval, 2.88–3.38) in 2014. UC:CD incidence ratio reduced from 8.9 to 1.0 over 30 years ( P < 0.001). A family history of IBD was reported in 3.0% of patients. Stricturing or penetrating disease was found in 41% and perianal disease in 25% of patients with CD. 5-aminosalicylate use was common in UC (96%) and CD (89%). Cumulative rates of surgery for CD were 20.3% at 1 year and 25.7% at 5 years, and the corresponding rates for UC were 1.8% and 2.1%, respectively. Mortality for CD and UC was not significantly different from the general population. Conclusions: In a population-based study in Hong Kong, prevalence of IBD is lower than in the west although comparable to that of other East Asian countries. Complicated CD is common. Overall mortality remains low in Asians with IBD. Abstract : Supplemental Digital Content is Available in the Text.